PENGARUH VERMIKOMPOS ABU TERBANG BATUBARA MENGGUNAKAN CACING TANAH Eisenia fetida TERHADAP KANDUNGAN N, P, K, DAN Pb - Alfarizky Aryonugroho; Nina Dwi Lestari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
The plan to build a coal-fired steam power plant is expected to increase. One of the wastes generated from coal-fired steam power plants is coal fly ash. The accumulation of coal fly ash can cause environmental pollution such as soil and groundwater pollution in the storage location. Vermicompost can be used for managing coal fly ash by utilizing earthworms as decomposers. Earthworms can increase the availability of nutrients such as nitrogen, phosphorus, and potassium and reduce the solubility of lead contained in coal fly ash. The purpose of this study was to determine the effect of vermicompost using earthworm Eisenia fetida on the content of nitrogen, phosphorus, potassium, and lead in coal fly ash. Â The study consisted of five treatments, with a total weight of 3 kg coal fly ash each. The results showed that mixing cow dung in vermicomposting of coal fly ash significantly increased N, P, K and decreased Â Pb in vermicompost.